The Role of Social Capital in Household Waste Management: A Case Study in Blunyahrejo Village - Zilfani Fuadiyah Haq (BKM Public Health and Community Medicine, 2024)
Purpose: This study analyzes household waste management behavior using the social capital theory approach. Methods: Field observations and surveys were conducted on 102 residents in Blunyahrejo Village using a questionnaire modified from various sources, and the data were analyzed descriptively. Results: The study shows that respondents with higher social networks and trust tend to manage waste better. Social networks in respondents' environments, such as activities with neighbors and meetings, facilitate information exchange about waste management. Peer-group effects in these meetings encourage residents to adopt pro-environment behaviors. High social trust also eases cooperation and unites the community. The study also finds that men and people with higher education tend to manage waste better and have higher social networks and trust. A concrete example of social networks in the study area is the waste management activities by farmer groups, demonstrating how social networks are leveraged to mobilize community cooperation. In this context, leaders or key persons play a crucial role in motivating, setting examples, and maintaining the strength of social networks. However, the study also notes a decline in participation in collective waste management activities, such as the neighborhood waste bank, post-COVID-19 pandemic. This indicates the importance of leaders in re-motivating the community and utilizing existing social capital for new initiatives. Conclusion: Effective waste management can be achieved by involving the local community in community-based waste management programs. Local leaders have a significant role in policy-making, determining the initial steps of community movements, and building and maintaining community spirit. Universities can collaborate with local governments to provide environmental education targeting less-educated communities. Local governments can facilitate the formation of social networks and trust within the community. Empowering women through community or female activist initiatives can increase awareness and participation of women in waste management issues.